Verses of Prohibition for Children: Perspectives from Tafsir Ibn Kathir and Tafsir Al-Azhar and Their Relevance to the Field of Educational Psychology - Jihad, Hanif Ruhul; Shobahiya, Mahasri; Maksum, Muh. Nur Rochim (Universitas Muhammadiyah Surakarta, 2023)
Children need a safe environment to explore and offer the support they need to learn and help them grow and develop. When children are curious about something, they will choose to explore it. Prohibitions expressed by parents to their children not to do something by saying